1992
DOI: 10.1016/0248-4900(92)90431-y
|View full text |Cite
|
Sign up to set email alerts
|

Directed movements of ciliary and flagellar membrane components: A review

Abstract: The ability to rapidly translocate polystyrene microspheres attached to the surface of a plasma membrane domain reflects a unique form of cellular force transduction occurring in association with the plasma membrane of microtubule based cell extensions. This unusual form of cell motility can be utilized by protistan organisms for whole cell locomotion, the early events in mating, and transport of food organisms along the cell surface, and possibly intracellular transport of certain organelles. Since surface mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…It is well established that, although the membrane of the primary cilium is continuous with the plasma membrane of the cell, it is a separate membrane domain with a unique complement of proteins (Bloodgood 1992). Numerous previous studies have shown the localization of specific receptors to the primary cilium in a variety of different cell types.…”
Section: The Journal Of Histochemistry and Cytochemistrymentioning
confidence: 99%
“…It is well established that, although the membrane of the primary cilium is continuous with the plasma membrane of the cell, it is a separate membrane domain with a unique complement of proteins (Bloodgood 1992). Numerous previous studies have shown the localization of specific receptors to the primary cilium in a variety of different cell types.…”
Section: The Journal Of Histochemistry and Cytochemistrymentioning
confidence: 99%
“…There is compelling evidence that intraflagellar transport is responsible for carrying flagellar precursors into newly forming flagella and for returning flagellar components to the cytoplasm during flagellar resorption. It is likely that this system also is involved in the constitutive turnover of flagellar components in intact cilia/flagella (78,(81)(82)(83)(84), although other motility mechanisms also may play a role (6,13,85).…”
Section: Regulated Translocation Of a Protein Into An Intactmentioning
confidence: 99%
“…Surface motility in Chlamydomonas cells includes gliding along substrates using flagellar membrane adherence, flagella-flagella contact between two cells during mating, and surface motility observed using polystyrene beads adhered to the flagellar membrane (for a review, see Bloodgood, 1992b). Flagellar surface motility is predicted to involve a microtubulebased motor protein associated with the flagellar membrane and linked to flagellar glycoproteins that adhere to a surface.…”
Section: A Fraction Of Crkcbp Localizes To Flagellamentioning
confidence: 99%